Implementasi Kebijakan Penyelenggaraan Identitas Kependudukan Digital di Dinas Kependudukan dan Pencatatan Sipil Kota Pekanbaru - Muhammad Rusydi; Dadang Mashur (Journal of Research and Development on Public Policy, 2024)
The aim of this research is to find out and explain how the policy for implementing digital population identity is implemented in the Pekanbaru city population and civil registration service. This research uses implementation theory (Edward III, 1980) which is divided into four indicators, namely Communication, Resources, Disposition and Bureaucratic Structure. This research was conducted using descriptive qualitative research methods, data collection was obtained through interviews. The results of this research show that the Pekanbaru City Population and Civil Registration Service has implemented the four indicators of successful implementation well. The factors that hinder the Pekanbaru City Population and Civil Registration Service are the lack of knowledge and awareness from the community regarding the importance of IKD, the community's infrastructure such as not having a smartphone, and data packages and networks that are sometimes problematic. Based on the results and discussion, researchers suggest that the Pekanbaru City Population and Civil Registration Service should be further intensified by maximizing social media platforms, making circulars as a form of strengthening the acceleration of IKD implementation.